Low Tortuosity 3D‐Printed Structures Enhance Reaction Kinetics in Electrochemical Energy Storage and Electrocatalysis. Issue 12 (11th December 2022) - Xue, Xinzhe; Lin, Dun; Li, Yat
Abstract : Low‐Tortuosity In article number 2200159, Yat Li, Dun Lin, and Xinzhe Xue, highlight the low‐tortuosity feature of 3D‐printed architectures supporting fast reaction kinetics. Half‐immersed structure in the liquid illustrates the diffusion channels that enable fast mass transfer, including ions, molecules, and gas bubbles in both gas and liquid phases.